Antihypertensive medication adherence and cardiovascular disease risk: A longitudinal cohort study. (March 2021) - Li, Jiqing; Zhang, Zhentang; Si, Shucheng; Wang, Bojie; Xue, Fuzhong
Abstract: Background and aims: Few studies estimated the impact of antihypertensive adherence on cardiovascular diseases (CVD) in a longitudinal cohort with presence of time-dependent confounders. This study aims to assess the association between antihypertensive adherence and CVD using marginal structural Cox model (MSM-Cox) and to characterize blood pressure (BP) trajectories of patients with different adherence. Methods: This longitudinal study included 16, 896 hypertensive patients receiving antihypertensive medication. The median follow-up time was 3.5 years (25th to 75th, 1.75–4.75 years). BP and medication adherence were measured four times every year. We used MSM-Cox and Cox model to assess association between antihypertensive adherence and CVD events. The linear mixed-effects model was used to characterize BP trajectories of patients with different adherence, and the area under curves (AUC) was calculated as BP burden. Results: We documented 4735 CVD events, crude incidence of CVD was 80.8 (95% CI, 78.1–83.4) and 112.6 (95% CI, 107.2–118.0) per 1000 person-years for baseline high-adherence and low-adherence, respectively. Compared with high adherence, the adjusted hazard ratio (HR) for association between low adherence with CVD was 1.75 (95%CI, 1.62–1.89) and 1.34 (95%CI, 1.26–1.42) based on the MSM-Cox and the Cox model, respectively. The BP burden and fluctuation range of BP trajectory in low-adherence patients were larger than those of high-adherence patients. Patients with high adherence got 28% greater reduction of BP burden than low-adherence patients. Conclusions: Antihypertensive adherence was more strongly associated with the risk of CVD than conventional regression analyses based on a single adherence measurement. Graphical abstract: Image 1 Highlights: We used marginal structure models (MSM) to evaluate the impact of antihypertensive adherence on cardiovascular diseases (CVD) risk in a longitudinal cohort. We used a linear mixed-effect model to describe blood pressure (BP) trajectory and estimated BP burden in patients with different adherence. Antihypertensive adherence had a stronger association with CVD than that of conventional analyses based on single measures. The BP burden and fluctuation of BP trajectory in low-adherence patients were larger than those of high-adherence patients.